THE MECHANISM FOR ADAPTING THE WORKING CAPITAL STRATEGY THROUGH THE IMPACT ON THE VOLUME AND PERIOD OF CIRCULATION OF WORKING CAPITAL (International Congress on Economics, Management and Business Studies, 2026)
The mechanism for adapting the working capital strategy is considered a complex, dynamic, and multi-level system of managerial influence aimed at ensuring the sustainable and efficient formation, allocation, and utilization of circulating assets under conditions of economic uncertainty, structural transformation, and continuous changes in macroeconomic parameters. In contemporary financial management theory, this mechanism is increasingly viewed not merely as an operational tool, but as a strategic component of financial decision-making that directly determines the long-term stability, competitiveness, and resilience of the enterprise.